The scene and theory between us and him, the self and the other (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Through this article, the author intended to carry out a self-reflection of his theoretical praxis. He also aimed to insert this praxis within a set of critical and analytical efforts by some other researchers. The main purpose was related to the attempt to circumscribe problems that the author has faced regarding the relationships between theatrical creation and collective identities and subjectivities (class, race, gender and others). This scope, revisited in the article, was also what was present in the successive projects of the ongoing research program on the subjectivities and policies of the contemporary scene that the researcher has been developing since 2009.
Keywords: theater theory; community; identity; opacity; subjectivation